If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (300 + x)(1500 + 9x) = 6 Multiply (300 + x) * (1500 + 9x) (300(1500 + 9x) + x(1500 + 9x)) = 6 ((1500 * 300 + 9x * 300) + x(1500 + 9x)) = 6 ((450000 + 2700x) + x(1500 + 9x)) = 6 (450000 + 2700x + (1500 * x + 9x * x)) = 6 (450000 + 2700x + (1500x + 9x2)) = 6 Combine like terms: 2700x + 1500x = 4200x (450000 + 4200x + 9x2) = 6 Solving 450000 + 4200x + 9x2 = 6 Solving for variable 'x'. Reorder the terms: 450000 + -6 + 4200x + 9x2 = 6 + -6 Combine like terms: 450000 + -6 = 449994 449994 + 4200x + 9x2 = 6 + -6 Combine like terms: 6 + -6 = 0 449994 + 4200x + 9x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(149998 + 1400x + 3x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(149998 + 1400x + 3x2)' equal to zero and attempt to solve: Simplifying 149998 + 1400x + 3x2 = 0 Solving 149998 + 1400x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 49999.33333 + 466.6666667x + x2 = 0 Move the constant term to the right: Add '-49999.33333' to each side of the equation. 49999.33333 + 466.6666667x + -49999.33333 + x2 = 0 + -49999.33333 Reorder the terms: 49999.33333 + -49999.33333 + 466.6666667x + x2 = 0 + -49999.33333 Combine like terms: 49999.33333 + -49999.33333 = 0.00000 0.00000 + 466.6666667x + x2 = 0 + -49999.33333 466.6666667x + x2 = 0 + -49999.33333 Combine like terms: 0 + -49999.33333 = -49999.33333 466.6666667x + x2 = -49999.33333 The x term is 466.6666667x. Take half its coefficient (233.3333334). Square it (54444.44448) and add it to both sides. Add '54444.44448' to each side of the equation. 466.6666667x + 54444.44448 + x2 = -49999.33333 + 54444.44448 Reorder the terms: 54444.44448 + 466.6666667x + x2 = -49999.33333 + 54444.44448 Combine like terms: -49999.33333 + 54444.44448 = 4445.11115 54444.44448 + 466.6666667x + x2 = 4445.11115 Factor a perfect square on the left side: (x + 233.3333334)(x + 233.3333334) = 4445.11115 Calculate the square root of the right side: 66.671666771 Break this problem into two subproblems by setting (x + 233.3333334) equal to 66.671666771 and -66.671666771.Subproblem 1
x + 233.3333334 = 66.671666771 Simplifying x + 233.3333334 = 66.671666771 Reorder the terms: 233.3333334 + x = 66.671666771 Solving 233.3333334 + x = 66.671666771 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-233.3333334' to each side of the equation. 233.3333334 + -233.3333334 + x = 66.671666771 + -233.3333334 Combine like terms: 233.3333334 + -233.3333334 = 0.0000000 0.0000000 + x = 66.671666771 + -233.3333334 x = 66.671666771 + -233.3333334 Combine like terms: 66.671666771 + -233.3333334 = -166.661666629 x = -166.661666629 Simplifying x = -166.661666629Subproblem 2
x + 233.3333334 = -66.671666771 Simplifying x + 233.3333334 = -66.671666771 Reorder the terms: 233.3333334 + x = -66.671666771 Solving 233.3333334 + x = -66.671666771 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-233.3333334' to each side of the equation. 233.3333334 + -233.3333334 + x = -66.671666771 + -233.3333334 Combine like terms: 233.3333334 + -233.3333334 = 0.0000000 0.0000000 + x = -66.671666771 + -233.3333334 x = -66.671666771 + -233.3333334 Combine like terms: -66.671666771 + -233.3333334 = -300.005000171 x = -300.005000171 Simplifying x = -300.005000171Solution
The solution to the problem is based on the solutions from the subproblems. x = {-166.661666629, -300.005000171}Solution
x = {-166.661666629, -300.005000171}
| 3+x+5x=3 | | 6m-3=9 | | 179-5x=40x+24 | | -116=-4w | | 3x^2+14=-13x | | 3x+2=9x-4 | | 12-(4)(-2)= | | 4x-8=2x+22 | | 74=26+8v | | -6y+30=-45 | | 100*10m=15m | | 10+7q=15+6q | | 2.6-8n=5n+19 | | 9+7x=6x+20 | | 8x-44=52 | | -0.2(x-6)=6 | | 11m^5= | | 4(d+2x)-5=3(3x+7) | | 7x-15=5x+7 | | 2c-5=c+9 | | x+x+81=x+144 | | -6+3w=-21 | | -6t-12-6t=10(t+5)+4 | | 2[1-3(w+2)+2(w+3)]=5w | | x-5-(-2)+2x=7 | | Q-2.4=1.8 | | 3b=6v+3b | | 10y+18=-3(5y-7)+5y | | 4n^2-4n-6=0 | | K-56=107 | | y+5=-7x-21 | | x^2-y^2-3x+3= |